Black lung : anatomy of a public health disaster - Derickson, Alan (Cornell University Press, 1998)
"Black Lung exposes the enormous human cost of producing the energy source responsible for making the United States the world's preeminent industrial nation. The book also provides a stark warning about the risks of ignoring or denying the existence of an occupational disease. Americans today are paying dearly for the decades when black lung was not recognized: compensation to disabled miners and their families has cost more than thirty billion dollars thus far. More important, society's denial of the dangers of coal mine dust shortened and impoverished the lives of miners, who today are too often breathless and displaced, destroyed by their work."--Jacket